2016
DOI: 10.1111/jdi.12524
|View full text |Cite
|
Sign up to set email alerts
|

Study on autonomic dysfunction and metabolic syndrome in Chinese patients

Abstract: Aims/IntroductionThere is still a lack of simple methods and instruments for the early assessment of autonomic dysfunction in metabolic syndrome patients. Assessment of sudomotor function has been proposed to explore autonomic function, and could be used as an early biomarker for metabolic syndrome. In the present study, we use a quick and non‐invasive method to measure sudomotor function, and aimed to evaluate its efficacy to identify metabolic syndrome in a Chinese population.Materials and MethodsInformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Future research studies to address whether improvements in cardiac autonomic function are sustained with lifestyle interventions and pharmacotherapy during follow-up are required [56, 160]. The use of risk scores for CAN to guide the timing of confirmatory tests for CAN and initiation of lifestyle or pharmacotherapy interventions requires exploration [19, 161]. Further research questions are summarised in Fig.…”
Section: Future Therapies and New Directionsmentioning
confidence: 99%
“…Future research studies to address whether improvements in cardiac autonomic function are sustained with lifestyle interventions and pharmacotherapy during follow-up are required [56, 160]. The use of risk scores for CAN to guide the timing of confirmatory tests for CAN and initiation of lifestyle or pharmacotherapy interventions requires exploration [19, 161]. Further research questions are summarised in Fig.…”
Section: Future Therapies and New Directionsmentioning
confidence: 99%
“…Autonomic dysfunction has been linked to target organ damage, such as diastolic dysfunction, ventricular hypertrophy or cardiac remodeling, as well as with insulin resistance, hyperinsulinemia, and dyslipidemia [13,15]. It has been postulated that prevention of autonomic dysfunction could be a strategy for reducing these comorbidities and that the assessment of autonomic function could be used as an early biomarker for metabolic diseases [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that there is an association between the number of components of metabolic syndrome, including the BMI, high blood pressure, high blood sugar, and dyslipidemia with autonomic dysfunction in patients without clinical evidence of peripheral or CAN ( Zhu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%